Model Pembelajaran Contextual Teaching Learning (CTL) pada Sekolah Dasar - Desy Rusminawati Amijaya; Iis Ristiani (Lembaga Pengembangan Kinerja Dosen, 2023)
This research is a preliminary research that contains efforts to apply the contextual teaching learning model at the elementary school level. This study also aims to determine student responses to the application of the contextual teaching learning model in grade 4 students of SD Negeri Pangestu. This study uses a research design with a